Effect of Moisture and Temperature on Thermal Conductivity of G2/04 Class Autoclaved Aerated Concrete - Pehlivanli, Zuhtu; Calin, Recep; Uzun, Ibrahim (Asian Journal of Chemistry, 2010)
In this study, the thermal conductivity value of G2/04 class autoclaved aerated concrete (AAC) material used as wall as in constructions and the change of material according as moisture and temperature were examined experimentally. The thermal conductivity value of autoclaved aerated concrete samples was measured experimentally in between 0 and 45 ºC temperatures and between 0 and 41.5 % moisture content. The thermal conductivity values of materials were measured according to the heat flow meter method using Lasercomp Fox 314 device. As a result of the study, it has been observed that the thermal conductivity of G2/04 class autoclaved aerated concrete material increased comparatively with temperature and moisture content. With the help of these experimental results, regression study was made for the change of thermal conductivity of G2/04 class AAC material according as the temperature and moisture content and k = 0.0926 + 0.00013 T + 0.00214 nm + 0.00007 T nm (W/m K) relation was obtained.